Financial Incentives for Green Energy Usage within the Scope of Sustainable Energy Policies: Survey Study with Production Companies in İzmir and Manisa - Atakan Gerger; Güneş Çetin Gerger; Devrim Şavlı (International Journal of Public Finance)
The increasing effects of global warming day by day lead to a gradual reduction of fossil fuel-based energy sources on a global scale, especially among European Union member countries. This situation has increased the orientation towards renewable energy sources and brought the circular economy to the forefront. The shift towards green energy sources also leads to changes in energy policies and encourages investment in green energy sources. This trend, along with the measures of international global organizations, has accelerated the green transformation of companies. With this research, financial incentives for sustainable energy sources and carbon-free energy in Turkey and worldwide have been examined. Problems and success factors that make compliance with the European Green Deal difficult, along with current regulations, were evaluated with the help of surveys. The sample universe consisted of companies located in the Manisa Organized Industrial Zone and companies located in Izmir affiliated with the Aegean Region Chamber of Industry. Through statistical analysis, the situations, attitudes of companies regarding green energy usage, and current problems and awareness regarding sustainable economy have been examined. The analysis revealed whether the companies in the sample group have sufficient knowledge about financial incentives related to green energy usage.